Characterization of flavor compounds and core functional microorganisms during pile fermentation of Liupao tea - Yanjun Chen; Yuelan Pang; Yueming Liang; Zhusheng Liu; Zhonghua Liu; Qiming Hu; Fujing Pan (Food Chemistry, 2026)

Combined effects of tropical and mid-high-latitude ISO on the dry- wet sudden transition in the mid-low reaches of the Yangtze River during boreal summer of 2015 - Yuchen Zhao; Shuangyan Yang; Pang-chi Hsu; Yanjun Qi (Climate Dynamics, 2026)

Viscosity-tunable polyvinyl alcohol/tannic acid supramolecular adhesive with ethanol as an intermolecular physical interaction modulator - Ninglu Zhang; Liangxian Liu; Yuyan Jiang; Haiyu Li; Na Wang; Ming Wei; Dexiu Min; Zhenqian Pang; Yanjun Xie; Jian Li; Shaoliang Xiao (Chemical Engineering Journal, 2026)

Mussel-inspired coating anchored polyquaternium functionalized nonwoven fabrics for microplastic adsorption - Yuanshuai Wan; Yanjun Jia; Yonggui Guo; Jianteng Sun; Maofeng Liang; Lichao Gao; Haidong Cao; Tiantian Liu; Hongxiang Zhao; Yuliang Pang; Yanwei Fu; Yu Zhao; et al. (Journal of Environmental Chemical Engineering, 2025)

Multifunctional conductive and antifreeze cellulose acetate-based zwitterionic hydrogel electrolytes for flexible foldable solid-state capacitors under extreme conditions - Yanjun Pang; Baolong Zhu; Gentan Xie; Wei Shen; Lixin Wang; Xinxin Luan; Dong Xie; Jinhui Pang (Carbohydrate Polymers, 2025)

Passivity-Based Sliding Mode Control for the Robust Trajectory Tracking of Unmanned Surface Vessels Under External Disturbances and Model Uncertainty - Luke Ma; Siyi Pang; Yao He; Yongxin Wu; Yanjun Li; Weijun Zhou (Journal of Marine Science and Engineering, 2025)
This study uses a port-Hamiltonian framework to address trajectory tracking control for unmanned surface vessels (USVs) under unknown disturbances. A passivity-based sliding mode controller is designed, integrating adaptive disturbance estimation and an RBFNN-based uncertainty estimator. Stability is rigorously proven, and simulations confirm superior tracking performance, strong disturbance rejection, and accurate uncertainty estimation.

Durable and degradable adhesive-free wood straw via cell wall activation and self-bonding - Liangxian Liu; Guoqing Mu; Haiyu Li; Haozhou Huang; Yuyan Jiang; Yutong Chen; Ming Wei; Dexiu Min; Jian Li; Yanjun Xie; Zhenqian Pang; Shaoliang Xiao (Chemical Engineering Journal, 2025)

MiR-497-5p ameliorates the oxyhemoglobin-induced subarachnoid hemorrhage injury in vitro by targeting orthodenticle homeobox protein 1 (Otx1) to activate the Nrf2/HO-1 pathway - Jun Zhu; Enyu Pan; Lujun Pang; Xiwei Zhou; Yanjun Che; Zhao Liu (Molecular Genetics and Genomics, 2024)

Mechanism of Antidepressant Action of (2R,6R)-6-Hydroxynorketamine (HNK) and Its Compounds: Insights from Proteomic Analysis - Chaohui Zhen; Chong Wang; Yanjun Ma; Yuli Pang; Feiyue Cai; Jiali Meng; Yuefei He; Ping Xiao; Jianxi Liu; Xi Mei; Shupeng Li; Guanzheng Wu; et al. (Molecular Neurobiology, 2024)

Cellulose eutecticgel electrolytes based on ethylene glycol/zinc chloride deep eutectic solvent for flexible solid-state capacitors - Yanjun Pang; Kefeng Zhang; Xinxin Luan; Baolong Zhu; Wei Shen; Congxia Xie; Lu Li; Jinhui Pang (Chemical Engineering Journal, 2023)

Adhesive injectable cellulose-based hydrogels with rapid self-healing and sustained drug release capability for promoting wound healing - Lu Li; Lixin Wang; Xinxin Luan; Yanjun Pang; Kefeng Zhang; Yushuai Cheng; Zhe Ji; Jinhui Pang (Carbohydrate Polymers, 2023)

Self-adhesive frost-resistant conductive hydrogel electrolytes based on TA@WSCA-Zn autocatalytic system for flexible and foldable solid-state capacitors - Yanjun Pang; Xinxin Luan; Kefeng Zhang; Yuxiang Liu; Lu Li; Congxia Xie; Jinhui Pang (Chemical Engineering Journal, 2023)

Particle size effects in microbial characteristics in thermophilic anaerobic digestion of cattle manure containing copper oxide - Yuanyuan Lu; Xuna Liu; Yanjun Miao; Efthalia Chatzisymeon; Lina Pang; Luqing Qi; Ping Yang; Hongyan Lu (Environmental Science and Pollution Research, 2022)

Suppression of MALAT1 alleviates neurocyte apoptosis and reactive oxygen species production through the miR-499-5p/SOX6 axis in subarachnoid hemorrhage - Xiwei Zhou; Bao Zheng; Lujun Pang; Yanjun Che; Xin Qi (Journal of Molecular Histology, 2022)

Accelerated changes of glaciers in the Yulong Snow Mountain, Southeast Qinghai-Tibetan Plateau - Shijin Wang; Yanjun Che; Hongxi Pang; Jiankuo Du; Zhonglin Zhang (Regional Environmental Change, 2020)
The Yulong Snow Mountain (YSM) is a region of temperate glaciers in the southeast Qinghai-Tibetan Plateau. The present study systematically assessed the glacier changes during the past several decades using ground-based and remotely sensed observations and referencing topographic maps. The images and maps revealed that the glaciers area in the YSM retreated by 64.02% from 1957 to 2017. The length of Baishui River Glacier No. 1 decreased by 12.5 m/year during this period, whereas the front elevation of this glacier increased by 10.83 m/year. The mean annual mass balance of this glacier was at − 0.42 metre water equivalent from 1957 to 2017, and its accumulative mass balance was − 27.45 metre water equivalent. The glacier retreats of glacier area, glacier front, and mass balance in the YSM primarily resulted from the increasing air temperature. These glacier retreats not only will have a negative impact on glacier tourism in the future, e.g., the retreat or disappearance of glaciers will reduce the attractiveness of mountainous scenic spots, but also will create new opportunities for the development of local tourism, e.g., “last chance” will simulate tourists’ curiosity. Hence, the findings of our present study help to understand the mechanism between accelerated ablation of temperate glaciers and climate change in southeast regions of Qinghai-Tibetan Plateau and provide references for local tourism administrations.

Glyphosate application increased catabolic activity of gram-negative bacteria but impaired soil fungal community - Yehao Liu; Yongchun Li; Xiaomei Hua; Karin Müller; Hailong Wang; Tongyi Yang; Qiong Wang; Xin Peng; Mengcheng Wang; Yanjun Pang; Jinliang Qi; Yonghua Yang (Environmental Science and Pollution Research, 2018)

Ectopic expression of cucumber (Cucumis sativus L.) CsTIR/AFB genes enhance salt tolerance in transgenic Arabidopsis - Zhehao Chen; Mengting Li; Ye Yuan; Jiangqin Hu; Yanjun Yang; Jiliang Pang; Lilin Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Transgenic analysis reveals LeACS-1 as a positive regulator of ethylene-induced shikonin biosynthesis in Lithospermum erythrorhizon hairy roots - Rongjun Fang; Fengyao Wu; Ailan Zou; Yu Zhu; Hua Zhao; Hu Zhao; Yonghui Liao; Ren-Jie Tang; Tongyi Yang; Yanjun Pang; Xiaoming Wang; Rongwu Yang; et al. (Plant Molecular Biology, 2016)

RfaB, a galactosyltransferase, contributes to the resistance to detergent and the virulence of Salmonella enterica serovar Enteritidis - Jing Su; Dommo Timbely; Minmin Zhu; Xiaomei Hua; Biao Liu; Yanjun Pang; Hengguan Shen; Jinliang Qi; Yonghua Yang (Medical Microbiology and Immunology, 2009)